Caracterização microestrutural e mecânica de trilhos ferroviários soldados de topo por caldeamento - Briguente, Claudemir Aparecido [UNESP] (2013)
It is known that the process of welding heat input due to interfere with the structure and mechanical behavior of the material factor that should be studied to better understand the mechanical and microstructural characteristics of these soldered joints and to compare these with the base metal changes to better understand the results. The study of this work was to investigate and discuss the results of microstructural and mechanical changes occurring in the cladding rails welded (ERW-HF, High Frequency Electric Resistance Welding). The welding process, despite its ease of implementation requires strict control of the parameters involved, including, preparation and alignment of parts, preheat control the application of electrical current for monitoring temperature control cooling after solder. Any deviation in these variables can cause defects such as grain growth, excessive hardness in the welded region, voids, among others, coupled with the severe conditions of loading imposed on the rail, to the passage of trains, cause the nucleation and the appearance of small compromising structurally broken rail. To prove the studies of microstructural characterization and mechanical rails welded ERW-HF assays were performed to analyze the chemical components of the material, ultrasound, three-point bending, micro and macro-hardness, metallography, tensile, and impact. The tests provide us with sufficient data to determine the behavior of the material, where the studies were concentrated in the region of the weld components focusing rail (head, web and foot), and these components regions classified as Base Metal (BM) Thermally Affected Zone (HAZ) and Line of Fusing (LF). With these results we conclude that the welded joint has suffered both micro structural changes, such as the mechanical behavior of the material in relation to the base metal, with cementite precipitated at grain boundaries in the LC, the less elastic deformation in the HAZ, and ...